Can retail banking clients’ attrition be managed? - Agaliotis, Konstantinos; Hadzic, Miroljub (Industrija, 2015)
The рurрοѕe of all banks across the universe is to satisfy their clients’ necessities. One of the predominant impacts of the last few years’ financial crisis in Europe was the way in which customers interact with their banks. The theory of “main bank” is not any more the case as clients’ trust toward banks fades away together with their loyalty. Nowadays, it is necessary for banks to segment their clientele data base, and target the most profitable clients. The retention stategy of each financial instiution becomes more and more important as the value of each retained customer is disproportional to the cost of acquiring a new one. The main findings of the subject retail banking clients’ retention policy analysis prove that clients of different lifetime value have different propensity to defect. At the same time, the ability of a bank to retain a potential defector does not depend directly on satisfying the defection reason. Many of the various bank counter offers which do not directly satisfy the reason that a client refers to as the “defection” one, are enough in order to retain a client